Romeo And Juliet In Baghdad: An Intertextual Study From A Contemporary Iraqi Perspective - H. Ubeid, Ahmed (Opción, 2019)
Literature is not concerned with certain nation. It is a product of experiences, philosophies and human trends towards best ways to understand life and ulti- mately to live peacefully. Global human issues are usually processed by differ- ent literary works that excite authors to assess certain values and beliefs among their communities. Ultimately, these assessments reflect what type of culture certain community has. By approaching to such human issues and studying the circumstances around them in the selected text, reasonable answers come simultaneously to understand the above mentioned experiences and human trends. By means of intertextuality, adaptation and appropriation, this study attempts to probe Monadhil Daoud Albayati’s Romeo and Juliet in Baghdad (2012) as an intertextual text of Shakespeare’s Romeo and Juliet (1596). In terms of structure and theme, the study reveals how the Shakespearean details framed Albayati’s play. Some similarities and differences are valuable due to social and cultural points of view each plot has. Such plays confront the au- dience with universal truths: conflict persists across mankind and it must be addressed before it spirals out of control. But most of all, the ambition to love and be loved is present in all times and places, whether in Baghdad or Verona, for lovers like Romeo and Juliet, or for brothers like Montague and Capulet.